2020
DOI: 10.34172/jept.2020.41
|View full text |Cite
|
Sign up to set email alerts
|

Delirium treatment in intoxicated patients in ICU: A randomized, double-blind clinical trial

Abstract: Objective: Delirium is one of the most common complications in patients admitted to intensive care units (ICUs). Delirium is a definite cause for more extended hospital stays, higher mortality rates, and possibly persistent cognitive decline in the future. Antipsychotics have been frequently evaluated as first drugs of choice, but the most appropriate, evidence-based treatment is yet to be discovered. This study aims to compare the efficacy of haloperidol and olanzapine in patients admitted to our toxicology I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Six studies 26 , 27 , 29 32 reported the incidence of complications under the use of olanzapine and other interventions. The overall complication rate of the olanzapine group was 14.74% (56/380), which was lower than the rate of 27.25% (112/411) in the other intervention groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies 26 , 27 , 29 32 reported the incidence of complications under the use of olanzapine and other interventions. The overall complication rate of the olanzapine group was 14.74% (56/380), which was lower than the rate of 27.25% (112/411) in the other intervention groups.…”
Section: Resultsmentioning
confidence: 99%
“…Six had unmeasured delirium, 31 post ICU/non-ICU occurrence, 21 study subjects nonolanzapine, 10 abstracts only, 15 reviews only, nine case/case series, 16 secondary analyses, six editorials/reviews, one descriptive study, seven terminated/incomplete, and 21 unclassified studies were excluded. Finally, nine quantitative studies (four RCTs and five retrospective cohort studies) 15,[26][27][28][29][30][31][32][33] were included. The main characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations